Completion Thyroidectomy for Initially Misdiagnosed Differentiated Thyroid Carcinoma-Study of 51 cases - Ghosh, Subrata; Kamal, Abu Hena Mostafa; Haque, Muhammad Mahamudul; Islam, Md Safiul; Islam, Md Asadul; Sarkar, Subrata Ranjan (TAJ: Journal of Teachers Association, 2020)
Introduction: Completion thyroidectomy is the removal of any residual thyroid tissue that remains after a less than total thyroidectomy. This procedure is usually done when the final histopathlogy of the excised ipsilateral thyroid lobe reveals papillary or follicular carcinoma. Objective: A retrospective analysis was done of patients undergoing completion thyroidectomy for thyroid malignancy who had undergone surgery elsewhere for solitary thyroid nodule. The incidence of complications in these patients after re-operation was investigated in this study. Material and Method: Our study included a total 51 patients who had undergone thyroid lobectomy for a solitary nodule as initial surgery in our hospital & elsewhere and were admitted in our hospital for completion thyroidectomy when histopathology revealed malignancy in last 5 years (2014-2018). Result: In this study-51 patients were enrolled; among them 42 were female and 9 male. Their mean age was 33.6 years (range-17-59 years). After initial surgery, the histopathology revealed papillary carcinoma in 45 patients (88.24%), follicular carcinoma in 6 patients (11.76%). Four out of 51 patients had recurrent laryngeal nerve palsy after initial surgery (7.8%). None of the patients had clinical hypocalcaemia after 1st surgery. Parathyroid glands are identified and preserved in all patients during completion thyroidectomy. No patient had additional recurrent laryngeal nerve injury in 2nd surgery. Mean follow-up was one year. Transient hypoparathyroidism occurred in 9.8% patients, but no permanent hypoparathyroidism. Seven patients were lost to follow-up. Conclusion: Completion thyroidectomy is a safe and appropriate procedure for the management of initially misdiagnosed differentiated thyroid carcinoma. TAJ 2019; 32(2): 22-26